Defining relative humidity in terms of water activity. Part 1: definition. (18th July 2017) - Feistel, Rainer; Lovell-Smith, Jeremy W
Abstract: Relative humidity (RH) is a quantity widely used in various fields such as metrology, meteorology, climatology or engineering. However, RH is neither uniformly defined, nor do some definitions properly account for deviations from ideal-gas properties, nor is the application range of interest fully covered. In this paper, a new full-range definition of RH is proposed that is based on the thermodynamics of activities in order to include deviations from ideal-gas behaviour. Below the critical point of pure water, at pressures p < 22.064 MPa and temperatures T < 647.096 K, RH is rigorously defined as the relative activity (or relative fugacity) of water in humid air. For this purpose, reference states of the relative activity are specified appropriately. Asymptotically, the ideal-gas limit of the new definition is consistent with de-facto standard RH definitions published previously and recommended internationally. Virial approximations are reported for estimating small corrections to the ideal-gas equations.